Introducing Groundwater. - Price, Michael (Senior Lecturer in Hydrogeology, University of Reading) (Taylor and Francis, 2013)
Presented in a style intended for the non-specialist reader, with technical terms and mathematical formulae kept to a minimum, the second edition of this introduction to groundwater covers a range of topics as they relate to hydrogeology. A major new chapter focuses on pollution.